REVEALING TAX AVOIDANCE IN THE FAMILY-OWNED COMPANY: ETHNOMETHODOLOGY STUDY - Maron, Wempi; Sukoharsono, Eko Ganis (Accounting Department,, 2016)
This paper dismantles the occurance of Tax Avoidance found in the family company in Malang. The method used in this research is etnomethodology, a method that is used to investigate indexical expressions and other practical actions as a unified settlement that is being done (the organized Tax Avoidance) and how to apprehed their everyday world. It is mentioned in the beginning that there are a number of factors which cause tax avoidance, that is a drive to